Changes in Ca2+ Removal Can Mask the Effects of Geometry During IP3R Mediated Ca2+ Signals - Piegari, Estefanía; Villarruel, Cecilia; Ponce Dawson, Silvina (Frontiers in Physiology, 2019)
Calcium (Ca2+) signals are ubiquitous. Most intracellular Ca2+ signals involve the release of Ca2+from the endoplasmic reticulum (ER) through Inositol 1,4,5-Trisphosphate Receptors (). The non-uniform spatial organization of IP3Rs and the fact that their individual openings are coupled via cytosolic Ca2+ are key factors for the variety of spatio-temporal distributions of the cytosolic [Ca2+] and the versatility of the signals. In this paper we combine experiments performed in untreated and in progesterone-treated Xenopus laevis oocytes and mathematical models to investigate how the interplay between geometry (the IP3R spatial distribution) and dynamics (the processes that characterize the release, transport and removal of cytosolic Ca2+) affects the resulting signals. Signal propagation looks more continuous and spatially uniform in treated (mature) than in untreated (immature) oocytes. This could be due to the different underlying IP3R spatial distribution that has been observed in both cell types. The models, however, show that the rate of cytosolic Ca2+ removal, which is also different in both cell types, plays a key role affecting the coupling between Ca2+ release sites in such a way that the effect of the underlying IP3R spatial distribution can be modified.